A core role for cognitive processes in the acute onset and maintenance of post‐traumatic stress in children and adolescents. (25th March 2019) - Meiser‐Stedman, Richard; McKinnon, Anna; Dixon, Clare; Boyle, Adrian; Smith, Patrick; Dalgleish, Tim
Abstract : Background: Post‐traumatic stress disorder (PTSD) is a common reaction to trauma in children and adolescents. While a significant minority of trauma‐exposed youth go on to have persistent PTSD, many youths who initially have a severe traumatic stress response undergo natural recovery. The present study investigated the role of cognitive processes in shaping the early reactions of child and adolescents to traumatic stressors, and the transition to persistent clinically significant post‐traumatic stress symptoms (PTSS). Methods: A prospective longitudinal study of youth aged 8–17 years who had attended a hospital emergency department following single trauma was undertaken, with assessments performed at 2–4 weeks ( N = 226) and 2 months ( N = 208) post‐trauma. Acute stress disorder and PTSD were assessed using a structured interview, while PTSS, depression severity and peritraumatic and post‐traumatic cognitive processes were assessed using self‐report questionnaires. On the basis of their PTSS scores at each assessment, participants were categorised as being on a resilient, recovery or persistent trajectory. Results: PTSS decreased between the two assessments. Cognitive processes at the 2‐ to 4‐week assessment accounted for the most variance in PTSS at both the initial and follow‐up assessment. The onset of post‐traumatic stress was associated particularly with peritraumatic subjective threat, data‐driven processing and pain. Its maintenance was associated with greater peritraumatic dissociation and panic, and post‐traumatic persistent dissociation, trauma memory quality, rumination and negative appraisals. Efforts to deliberately process the trauma were more common in youth who experienced the onset of clinically significant PTSS. Regression modelling indicated that the predictive effect of baseline negative appraisals remained when also accounting for baseline PTSS and depression. Conclusions: Cognitive processes play an important role in the onset and maintenance of PTSS in children and adolescents exposed to trauma. Trauma‐related appraisals play a particular role when considering whether youth make the transition from clinically significant acute PTSS to persistent PTSS. Abstract : Read the Commentary on this article at doi:10.1111/jcpp.13081